(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the acute toxicity assessment of Curcuma rangjued extracts (GERC7) in mice. Methodology: Acute toxicity testing was conducted in accordance with the OECD guideline 420 and the Vietnamese Ministry of Health’s Guidelines for preclinical and clinical testings of traditional medicine and herbal drugs on October 27, 2015. Results: At doses of 75 mL/kg/day, GERC7 did not cause acute toxicity in white mice via oral administration. Conclusions: Curcuma rangjued is a promising medicinal resource, proven to be safe and non-toxic at doses up to 75 mL/kg/day in experimental mice, when the extract is produced by steam distillation to create the GERC7.